Modified stall‐side crossmatch for transfusions in horses. (18th May 2019) - Casenave, Pauline; Leclere, Mathilde; Beauchamp, Guy; Blais, Marie‐Claude
Abstract: Background: After‐hours or out‐of‐clinic crossmatches are often limited by the lack of access to specialized material and technical expertise. Hypothesis/Objectives: The goal was to adapt a stall‐side crossmatch test for pretransfusion evaluation in horses. Animals: Twelve healthy mares (plasma and blood donors, teaching mares). Methods: In a prospective study, blood from 12 mares was used to compare the results of 132 crossmatches performed with a rapid gel assay to crossmatches performed with a microgel column assay, and with predicted compatibilities based on blood types and detection of antibodies at a reference laboratory (microplate assay). The rapid gel assay protocol for dogs was adapted to decrease the formation of rouleaux that initially precluded equine erythrocytes migration through the gel. Results: There was a good agreement between the rapid gel assay and the microgel assay as well as with the predicted compatibilities (κ > .6 for both). Agreement was higher between the microgel assay and the predicted compatibilities (κ = .8). The rapid gel assay failed to detect 6 predicted Aa incompatibilities (agglutinins‐related), 3 of which were also not detected with the microgel assay. Conclusions and Clinical Importance: Based on these results, the modified rapid gel assay could be useful in settings when access to the microgel assay is not available. Discrepancies between both gel techniques and predicted compatibilities were most often low‐grade agglutination, which warrants further investigation to assess their clinical importance.